2005
DOI: 10.1002/app.21485
|View full text |Cite
|
Sign up to set email alerts
|

Drying biodegradable poly(hydroxybutyrate‐co‐3‐hydroxyvalerate) gels in the elongated state to improve their mechanical properties

Abstract: ABSTRACT:Polyhydroxyalkanoates are a class of biodegradable polymers that may be used more as environmentally friendly materials if their mechanical properties can be improved. We approached this goal by modifying poly(3-hydroxybutyrate-co-3-hydroxyvalerate) with a well-established processing technique involving crosslinking the polymer chains and then drying a swollen gel of the network under uniaxial strain. The mechanical properties of the resulting oriented films were determined in continuous extension as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We have now found that lactones, such as GVL, γ‐butyrolactone and δ‐valerolactone, are able to dissolve up to 20 wt% of PHB in 1 min at temperatures above 100 °C, subsequently thickening to form a gel‐like material when the solution is cooled (seven‐membered ring lactones such as ϵ‐caprolactone did not dissolve PHB even under more severe conditions). This behavior was already described for other solvents such as chloroform, dimethylformamide, dimethyl sulfoxide (DMSO), dimethyl carbonate (DMC) and methyl isobutyl ketone . Since the addition of plasticizers can improve thermal and mechanical properties of the copolymer P(3HB‐3HV), TEC was used to enhance gel handling, increasing the overall greenness; TEC in fact, is a non‐toxic, bio‐based and biodegradable plasticizer, thus its use is highly advantageous respect to the health‐concerning phthalates …”
Section: Introductionmentioning
confidence: 85%
“…We have now found that lactones, such as GVL, γ‐butyrolactone and δ‐valerolactone, are able to dissolve up to 20 wt% of PHB in 1 min at temperatures above 100 °C, subsequently thickening to form a gel‐like material when the solution is cooled (seven‐membered ring lactones such as ϵ‐caprolactone did not dissolve PHB even under more severe conditions). This behavior was already described for other solvents such as chloroform, dimethylformamide, dimethyl sulfoxide (DMSO), dimethyl carbonate (DMC) and methyl isobutyl ketone . Since the addition of plasticizers can improve thermal and mechanical properties of the copolymer P(3HB‐3HV), TEC was used to enhance gel handling, increasing the overall greenness; TEC in fact, is a non‐toxic, bio‐based and biodegradable plasticizer, thus its use is highly advantageous respect to the health‐concerning phthalates …”
Section: Introductionmentioning
confidence: 85%
“…PLA itself is a hard and brittle plastic with high modulus, high strength, but low elongation at break (about 5%) 1–3. Because many of the body tissues have high elasticity, network polyester elastomers are gradually replacing the traditional linear materials 4–7. For drug delivery purpose, the presence of crosslinks not only leads to excellent physical properties, but also increases degradation tendencies by eliminating (or minimizing) crystalline structure.…”
Section: Introductionmentioning
confidence: 99%